Kajian Teologis dan Yuridis Sistem Pendidikan menurut Struktur Teks Kejadian 1:1-31 - Karlau, Sensius Amon (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
The implementation of education which refers to the juridical foundation set by the government has an impact on the sustainability of theological and Christian colleges in their communitarians because of the consideration of theological studies according to their scientific learning outcomes. the fundamental problem to be researched is how the creation story at the beginning of the bible provides a perspective on the educational system which is understood as a theological study. This study aims to enrich the understanding of the education system based on theological and juridical studies as an educational reference for mutual realization between the two. The author uses the narrative and structural analysis method with a lexical observation approach to the structure and narrative of the text of Genesis 1: 1-31 to conclude that theological and juridical studies are not contradictory but complement each other in the actualization of education by humans with a loving attitude lev?vk? or “heart”, n?fšek? or “soul” and me'?d?k? or his power to love his Creator.